Optimizing the Role of MSMEs in Maintaining Stability of the Pagertanjung Village Community, Ploso District, Jombang Regency in the New Normal Era - Faisol Hamid; Aditya Harja Nenggar (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
MSMEs can improve the community's economy. MSMEs can create community creativity and create new markets. The problem found in Pagertanjung Village, Ploso District, is that there are still at least MSMEs. The survey results state that some of them have an interest but still have not found the idea and motivation to open a business. There are also those who have no interest in opening a business because their profession is a farmer. Therefore, we provide two solutions. First, provide training by processing natural resources that are easily found in Pagertanjung Village, Ploso, namely bananas. Banana processing training is given once a week with different recipes, namely banana brownies. The benefit of this training is that business actors can create accounts and market their products more broadly. The public can also increase their knowledge. It is hoped that this training can provide ideas and motivation for the community to open a business so that it can improve the economy of Pagertanjung Village, Ploso.